Modelo de programação não-linear para otimização do padrão de cultivo e retorno financeiro em áreas irrigadas - Monteiro, Raimundo Nonato Farias [UNESP] (2014)
The technique of irrigation aims at increasing crop yields, especially in regions where water scarcity is a limiting factor to production, however, has an expressive impact on the water availability of water sources, it requires the captation of a large volume of water due consumption required by crops. Proper irrigation management benefits the producer with reducing the cost of production and all water users due to economy this resource and other advantages arising from their efficient use. A rational way to define optimal plans of cultivation, as well as choose a water slide that be economically viable and productive among all the existing options, is the use of techniques that help in decision making, and the techniques of linear programming and nonlinear are powerful tools that can be used for the optimal allocation of these resources. This research aims to propose optima plans of cultivation, using the techniques of nonlinear programming, which provide the maximization of net return of Farm Olhos D'Agua, on Paranapanema - SP, allying the constraints of water availability, land and market, as well how to study the effects of different annual volumes of water available over the net income from the property. The model consists of an objective function, which is subject to restrictions on use of crop area and water resources as well as constraints in crop production and aim to maximization the sum of net benefits stemming from the production of crops in agricultural year 2013/2014. The optimized value of the financial returns of Olhos D'água farm was R$ 746.988,69, for the agricultural year 2013/2014, and presented the following cropping pattern in its optimal solution: 60 ha of cotton, 205 ha of beans, 119 ha of maize, 138 ha of soybeans planted in September and 112 ha of soybeans planted in December to ...